Mitochondrial Dynamics: Fission and Fusion in Fate Determination of Mesenchymal Stem Cells - Ren, Lin; Chen, Xiaodan; Chen, Xiaobing; Li, Jiayan; Cheng, Bin; Xia, Juan (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) are pivotal to tissue homeostasis, repair, and regeneration due to their potential for self-renewal, multilineage differentiation, and immune modulation. Mitochondria are highly dynamic organelles that maintain their morphology via continuous fission and fusion, also known as mitochondrial dynamics. MSCs undergo specific mitochondrial dynamics during proliferation, migration, differentiation, apoptosis, or aging. Emerging evidence suggests that mitochondrial dynamics are key contributors to stem cell fate determination. The coordination of mitochondrial fission and fusion is crucial for cellular function and stress responses, while abnormal fission and/or fusion causes MSC dysfunction. This review focuses on the role of mitochondrial dynamics in MSC commitment under physiological and stress conditions. We highlight mechanistic insights into modulating mitochondrial dynamics and mitochondrial strategies for stem cell-based regenerative medicine. These findings shed light on the contribution of mitochondrial dynamics to MSC fate and MSC-based tissue repair